Overexpression of a White Clover WRKY Transcription Factor Improves Cold Tolerance in Arabidopsis - Shuaixian Li; Meiyan Guo; Wei Hong; Manman Li; Xiaoyue Zhu; Changhong Guo; Yongjun Shu (Agronomy, 2025)
Plants are frequently exposed to various abiotic stresses, among which low-temperature stress markedly impairs growth and physiological functions. WRKY transcription factors are key regulators in plant responses to abiotic stress. In this study, a novel WRKY transcription factor gene, TrWRKY79, was cloned from white clover. Functional characterization revealed that the full-length TrWRKY79 protein possesses typical features of transcription factors, including transcriptional activation activity located at its C-terminal domain. Heterologous expression of TrWRKY79 in Arabidopsis thaliana significantly enhanced cold tolerance under low-temperature stress. Physiological assays showed that the transgenic lines exhibited higher chlorophyll content and elevated activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) compared to wild-type plants. Furthermore, Protenix was employed to predict the potential target genes of TrWRKY transcription factors, and their expression profiles were analyzed to help elucidate the regulatory network underlying cold tolerance. qRT-PCR analysis confirmed that several cold-responsive genes, such as COR47 and ABI5, were significantly upregulated in the transgenic lines. Collectively, these findings indicate that TrWRKY79 plays a positive regulatory role in enhancing cold tolerance, providing valuable insights into the molecular mechanisms of cold resistance in white clover and offering promising candidate genes for improving stress resilience in forage crops.